Nutritional Content of Fermented Cassava (Manihot esculenta crantz) Peel Using Cattle Rumen Waste - Dwi Handayani, Hesti; Purwati, Catur Suci; Yakin, Engkus Ainul; Husein, Muhammad (Universitas Veteran Bangun Nusantara, 2024)
This research aims to determine the effect of cow rumen waste on the nutritional value of cassava skin by increasing the values of dry matter content, crude fibre content and soluble protein content. This study used a unidirectional, completely randomized design (CRD) with four treatments and four replications. Then, the analysis was repeated two times. Fermentation was carried out for seven days. The treatment is P0 = 50 gram cassava peel + 14% bran + 2% molasses + 0% rumen waste, P1 = 50 gram cassava peel + 14% bran + 2% molasses + 2% rumen waste, P2 = 50 gram cassava peel + 14% rice bran + 2% molasses + 4% rumen waste, P3 = 50 gram cassava peel + 14% bran + 2% molasses + 6% rumen waste. The parameters observed in this study were the Dry Matter content (DW), Crude Fiber content (SK), and Soluble Protein content (PT). The results of measuring the dry matter content of P0, P1, P2 and P3 were achieved respectively, 33.92%, 38.88%, 43.20% and 51.20%. The crude fiber content results P0, P1, P2, P3 were achieved respectively at 0.41%, 0.72%, 1.16% and 1.49%. The results of dissolved protein levels P0, P1, P2 and P3 were achieved respectively at 5.11%, 5.17%, 5.73% and 7.20%. The research concluded that fermentation for seven days using cow rumen waste significantly affected the dry matter content, crude fibre content and soluble protein content of cassava peel.